2021
DOI: 10.3389/fpsyg.2020.564403
|View full text |Cite
|
Sign up to set email alerts
|

Score-Guided Structural Equation Model Trees

Abstract: Structural equation model (SEM) trees are data-driven tools for finding variables that predict group differences in SEM parameters. SEM trees build upon the decision tree paradigm by growing tree structures that divide a data set recursively into homogeneous subsets. In past research, SEM trees have been estimated predominantly with the R package semtree. The original algorithm in the semtree package selects split variables among covariates by calculating a likelihood ratio for each possible split of each cova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…These methods divide a data set into homogeneous subgroups by finding covariates that predict parameter differences. For SEMs, model-based recursive partitioning was popularized as SEM trees and gained attention in the past years [43][44][45]. Finally, it is important to note that the performance of IPC regression depends primarily on the available covariates.…”
Section: Discussionmentioning
confidence: 99%
“…These methods divide a data set into homogeneous subgroups by finding covariates that predict parameter differences. For SEMs, model-based recursive partitioning was popularized as SEM trees and gained attention in the past years [43][44][45]. Finally, it is important to note that the performance of IPC regression depends primarily on the available covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the score-guided SEM tree comes as a remedy for multiple ML comparisons by proposing an additional five methods. One simulation study found that two score-guided methods, i.e., maxLMO and CvM, outperformed ML methods in terms of statistical power, reducing computational time, and group recovery when examining multiple parameters (Arnold et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the score-guided SEM tree comes as a remedy for multiple ML comparisons by proposing an additional five methods. One simulation study found that two score-guided methods, i.e., maxLMO and CvM, outperformed ML methods in terms of statistical power, reducing computational time, and group recovery when examining multiple parameters (Arnold et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, an SEM tree package was used to construct the tree. The updated score-guided SEM tree, particularly maxLMO, controlled the tree depth (Arnold et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%